Can Conflict Resolution Effectively Deal With Terrorism? Critical Overview of Contemporary Challenge to International Security. - Frichand, Ana; Gjurovski, Marjan (Универзитет „Св. Климент Охридски“, Битола, Факултет за безбедност - Скопје, 2018)
This paper focuses on the dilemma whether conflict resolution can effectively deal with terrorism. It also question the potential of conflict resolution to extinguish terrorism. Some authors argue that conflict resolution has nothing to do with this phenomenon. They further say that negotiating with terrorists legitimizes their groups, goals and means. Therefore, talking to them would incite even more violence and weaken the democracy. However, there are others who believe in the opposite, i.e. that specific conflict resolution approach aimed towards resolving complex and fluid terrorist behavior have to be considered as part of a wider counter-terrorist strategy. Conflict resolution approach offers an innovative path toward understanding terrorism by engaging with it as a form of violence that is part of a broader conflict. Thus, the present paper provides critical overview of this contemporary challenge to international security and discuss why conflict resolution is crucial for an effective counter-terrorist intervention.
Keywords: conflict resolution, terrorism, international security, counter-terrorist intervention